THE EFFECTIVENESS OF THE USE OF SCRAMBLE METHOD IN CLASS IV IPS LEARNING SDN 1 BULANGO SELATAN BONE BOLANGO DISTRICT - HARIS MAHMUD; DIAH PERMATA SARI IMBA (International Journal of Innovations in Engineering Research and Technology, 2021)
The problem in this research is "Is the use of scramble method effective in social studies learning for class IV SDN 1 Bulango Selatan, Bone Bolango Regency?". The purpose of this study was to determine the effectiveness of using the scramble method in the fourth grade social studies learning at SDN 1 Bulango Selatan, Bone Bolango Regency. This study uses an evaluation method with a descriptive qualitative type of assessment. The research data were collected using observation, interview, documentation and test techniques.The results of the study concluded that the use of the scramble method was effective in social studies learning. This can be seen from the indicators of effectiveness which include learning outcomes, quality of learning, time effectiveness, teacher motivation, material organization, and class management abilities. When compared between before and after using the scramble method, there was a significant increase.